Corchorus olitorius (Jute) fiber enforced sustainable polymeric dressing material for antimicrobial activity - Gupta Swati Sanjaykumar; Rishabha Malviya; Dhanalekshmi Unnikrishnan Meenakshi; Sathvik Belagodu Sridhar (Medicine in Novel Technology and Devices, 2025)
Drug delivery to wounds has developed over time from the rudimentary administration of medication on the wound or the site of infection to more sophisticated drug delivery systems. For effectively and rapidly curing wounds, a diverse range of anti-bacterial drug delivery systems must be developed. The current study investigates the possibility of using an inexpensive and environment-friendly sustainable Corchorus olitorius fiber (COF) as a drug carrier for the antibacterial drug tetracycline HCl and its potential as a dressing material. The fibers were purified, grafted using acrylamide monomer, and tested for SEM, FT-IR, TGA, swelling index, swelling-de- swelling behavior, and chemical resistance. Drug loading was carried out, the highest drug loading percentage was found at 99.97 ​% and the formulation released medication according to the Baker-Lonsdale release kinetics pattern. The anti-microbial study showed effective inhibition of Staphylococcus aureus. The study demonstrates the successful synthesis and application of acrylamide-grafted COF loaded with tetracycline HCl, showcasing its potential as an effective wound dressing for wound care and management. Corchorus olitorius fiber is a cost-effective and eco-friendly material for preparing medicated polymeric dressings.